Evaluation of anti-inflammatory, analgesic, and antipyretic activities of the ethanol extract from Murdannia loriformis (hassk.) Rolla Rao et Kammathy - Phraepakaporn Kunnaja (2018)
© 2014 The Author(s). Introduction: Murdannia loriformis (hassk) Rolla Roa et Kammathy, family Commelinaceae, is used by Chinese practitioners as a remedy for cancer in an early stage, and also for treating other diseases including colds, throat infections, pneumonia, diabetes mellitus, flu and inflammation. Although anticancer as well as other pharmacological effects of M. loriformis have been reported, its anti-inflammatory and other activities related to inflammation are still limited. Methods: The anti-inflammatory activity was evaluated using carrageenan- and arachidonic acid-induced paw edema in rats, and cotton pelletinduced granuloma formation in rats. The analgesic and antipyretic activities were determined by formalin test in mice and yeast-induced hyperthermia in rats, respectively. Results: The ethanol extract of the aerial part of M. loriformis exhibited anti-inflammatory activity on the rat paw edema induced by carrageenan and arachidonic acid. It also showed an inhibitory effect on the granuloma and the transudative formation of the rat implanted with cotton pellets as well as lowered the elevated serum alkaline phosphatase activity to normal level. It exerted potent analgesic effect on both the early and late phase of formalin test as well as the antipyretic effect on yeast-induced hyperthermic rats. The oral single high dose of the extract of 5,000 mg/Kg did not produce death or any abnormalities or changes of the internal organs of rats during 14 days of the observed period. Conclusion: The results obtained from this study support the use of the plant in traditional medicine for inflammatory ailments.